2001
DOI: 10.1089/152091501750220019
|View full text |Cite
|
Sign up to set email alerts
|

Electrogastrography: Physiological Basis and Clinical Application in Diabetic Gastropathy

Abstract: Electrogastrography is the recording and measurement of gastric myoelectrical activity from electrodes placed on the surface of the epigastrium. Normal electrogastrograms (EGGs) reflect 3 cycles per min (cpm) gastric myoelectrical activity produced by specialized pacemaker cells, the interstitial cells of Cajal, located in the muscular wall of the gastric corpus and antrum. Gastric dysrhythmias (tachygastrias and bradygastrias) are disturbances of the normal gastric pacesetter potentials and are associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 36 publications
3
96
0
1
Order By: Relevance
“…If endoscopy and radionuclide scintigraphy are inconclusive, a small bowel contrast study should be performed to rule out possible mechanical lesions and/or generalized gut hypomotility. Although not routinely available [20] , electromyography of the gastrointestinal tract may provide valuable assistance in the diagnosis of patients with complex motility disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If endoscopy and radionuclide scintigraphy are inconclusive, a small bowel contrast study should be performed to rule out possible mechanical lesions and/or generalized gut hypomotility. Although not routinely available [20] , electromyography of the gastrointestinal tract may provide valuable assistance in the diagnosis of patients with complex motility disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary measures and prokinetic drugs may help relieve the symptoms in most patients, while some patients with severe nausea and vomiting require antiemetic medications. A few patients fail medical therapy and continue to have debilitating symptoms of gastroparesis, who may benefit from a venting gastrostomy [18] or jejunostomy performed surgically, endoscopically, or fluoroscopically [20] . Near-completion gastrectomy (NCG) has proved useful in small series of patients [21] , but data on longterm follow-up has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found no difference in EGG parameters between dyspeptic patients and healthy volunteers [6,7] . Patients with systemic diseases such as Parkinson's disease [8] , myotonic dystrophy [9] , and diabetes mellitus [10] show abnormal EGG findings. However, in patients with progressive systemic sclerosis (which is usually associated with poor gut motility), EGG shows unchanged parameters [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of abnormal ECA propagation patterns was found to be associated with gastric outlet obstruction (Brzana et al 1998, Smith et al 2003, gastroparesis (Smith et al 2003), gastric myoelectrical dysrhythmia (Qian et al 2003), atrophy and hypertrophy (Bortoff and Sillin 1986), diabetic gastropathy (Koch 2001) and Chagas disease (Madrid et al 2004), although no statistically significant differences were found between normal and abnormal EGG-recorded ECA patterns for human cases of achalasia (Verhagen et al 1998) and dysmotility-like functional dyspepsia (Oba-Kuniyoshi et al 2004, van der Voort et al 2003.…”
Section: Introductionmentioning
confidence: 99%